OBLIGATIONS OF PARENTS IN PROVIDING ISLAMIC RELIGIOUS EDUCATION FOR CHILDREN IN HUTA V NAGORI BANDAR TINGGI BANDAR MASILAM DISTRICT SIMALUNGUN REGENCY - Sari Atika Parinduri; Dita Wulandari Nst (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
Type This research is a type of qualitative descriptive research.The results of the research in this thesis,The obligation of parents to provide Islamic religious education for children in Huta V Nagori Bandar Tinggi, Bandar Masilam District, Simalungun Regency is first, the obligation of parents to provide Islamic religious education is to set a good example for a child. Second, teach directly how to worship properly such as obligatory prayers, fasting, giving alms, respecting older people, and teaching love to those who are younger. Third, invite children to participate in religious activities such as recitation and so on. Fourth, give gifts or rewards, because giving rewards to a child can be a separate motivation for a child. Fifth, by instructing a child to carry out an Islamic attitude from easy things such as saying alhamdulillah after eating, prayers before eating, reading prayers before and after waking up and so on. The results of the research analysis show that children in Huta V Nagori Bandar Tinggi attend many congregational prayers at the mosque when the Maghrib prayer starts, whereas during the Isha prayer only a few only pray in the mosque. This is because parents rarely invite their children to pray at the time of the Isya prayer. In addition, the lack of understanding from some village communities as parents regarding the obligation of Islamic religious education for their children resulted in a lack of knowledge of children regarding the obligation to pray the five times a day. that many children in Huta V Nagori Bandar Tinggi attend the congregational prayers at the mosque when the Maghrib prayer starts, while during the Isya prayer only a few attend the prayer at the mosque. This is because parents rarely invite their children to pray at the time of the Isya prayer. In addition, the lack of understanding from some village communities as parents regarding the obligation of Islamic religious education for their children resulted in a lack of knowledge of children regarding the obligation to pray the five times a day. that many children in Huta V Nagori Bandar Tinggi attend the congregational prayers at the mosque when the Maghrib prayer starts, while during the Isya prayer only a few attend the prayer at the mosque. This is because parents rarely invite their children to pray at the time of the Isya prayer. In addition, the lack of understanding from some village communities as parents regarding the obligation of Islamic religious education for their children resulted in a lack of knowledge of children regarding the obligation to pray the five times a day.